The Seperation of Power: An Experiment of Theory and Practice - Dahal, Gopal Prasad (Tribhuvan University Journal, 2013)
When the legislative and executive power united in the same person, or in the same body of magistrates, there can be no liberty ... Again, there is no liberty if the power of judging is not separated from the legislative and executive. If it were joined with the legislative, the life and liberty of the subject would be exposed to arbitrary control; for the judge would then be the legislator. If they were joined to the executive power, the judge might behave with violence and oppression. There would be an end to everything, if the same man or the same body, whether of the nobles or the people, where to exercise those three powers, that of enacting laws, that of executing public affairs, and that of trying crimes or individual causes. (Baron Montsquieu, 1989-1755).